ANKYLOSING SPONDLITIS IN WOMEN: CASE REPORT - SSK Göztepe Eğitim Hastanesi Fizik Tedavi ve Rehabilitasyon Kliniği 2Sonomed Görüntüleme Merkezi, (Archives of Rheumatology, 2003)
Ankylosing spondilitis is a chronic systemic inflammatory disorder of uncertain aetiology that primarily affects the axial skleton. The underdiagnosis of AS among women is a common problem probably owing to the misconception that women rarely have AS. Besides, the diagnosis of AS before the occurence of irreversible damage is difficult, several years may pass between onset of symptoms and definite diagnosis. We present the case of a 49-year-old woman who was initially diagnosed as spondylodiscitis due to severe low back pain for the last 3 months and high erythrocyte sedimentation rate. She had a medical history of laminectomy 10 years ago and low back pain for more than 10 years. After a careful physical and radiological examination it was clear that she had ankylosing spondylitis. The diagnosis of AS should always be kept in mind in women with chronic low back pain .